2019
DOI: 10.1039/c9dt02831e
|View full text |Cite
|
Sign up to set email alerts
|

Structure and bonding in reduced boron and aluminium complexes with formazanate ligands

Abstract: A comparison of structure and bonding in reduced formazanate B/Al complexes and their ligand-benzylated products is described. The kinetics of homolytic N–C(benzyl) bond cleavage in the latter compounds is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…[1][2][3] Formazanates have garnered considerable attention in coordination chemistry due to their ligand-based redox processes, which may facilitate multielectron redox transformations, [4] bond activations [5] and excited-state charge separation. [6] Av ariety of formazanate complexes of many main-group metals [7][8][9][10][11][12][13][14][15][16] andf irst-and second-row transition metals [17][18][19][20][21][22][23] have been described.T hese studies demonstrate the versatile coordination chemistry of formazanate ligandsa nd provides ignificant insight into the opticala nd redox properties of these compounds.S ome coppercomplexesc an also mediate oxygen activation, [24,25] certain cobalt and iron complexes exhibit unique magnetic characteristics, [17,26] and boronc omplexes in many cases feature not only the tunable redoxp roperties but also visible to nearinfrared photoluminescence, [9][10][11][12][13] finding applicationsa sc ellimaging agents [27,28] and electrochemiluminescence emitters. [10] Our group has expanded the coordination chemistry of formazanatest ot hird-row transition metals with as eries of hetero-leptic cyclometalated platinumc omplexes and bis-cyclometalated iridium complexes, [29][30][31] and accessed homoleptic azo-iminate platinum complexes and azo-1,2,3-triazolide iridium complexesv ia hydrogenative cleavage or [3+ +2]...…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Formazanates have garnered considerable attention in coordination chemistry due to their ligand-based redox processes, which may facilitate multielectron redox transformations, [4] bond activations [5] and excited-state charge separation. [6] Av ariety of formazanate complexes of many main-group metals [7][8][9][10][11][12][13][14][15][16] andf irst-and second-row transition metals [17][18][19][20][21][22][23] have been described.T hese studies demonstrate the versatile coordination chemistry of formazanate ligandsa nd provides ignificant insight into the opticala nd redox properties of these compounds.S ome coppercomplexesc an also mediate oxygen activation, [24,25] certain cobalt and iron complexes exhibit unique magnetic characteristics, [17,26] and boronc omplexes in many cases feature not only the tunable redoxp roperties but also visible to nearinfrared photoluminescence, [9][10][11][12][13] finding applicationsa sc ellimaging agents [27,28] and electrochemiluminescence emitters. [10] Our group has expanded the coordination chemistry of formazanatest ot hird-row transition metals with as eries of hetero-leptic cyclometalated platinumc omplexes and bis-cyclometalated iridium complexes, [29][30][31] and accessed homoleptic azo-iminate platinum complexes and azo-1,2,3-triazolide iridium complexesv ia hydrogenative cleavage or [3+ +2]...…”
Section: Introductionmentioning
confidence: 99%
“…[46][47][48][49][50] However, nitrogen inversion is an intra-molecular process that would be expected to have an activation entropy close to zero, or (in the case of highly strained systems) a slightly negative value. [46][47][48] Although 45 In this compound, the organic cation Bu 4 N + does not interact with the [ Bn 1] − moiety other than through electrostatic interactions (i.e., it forms a solvent-separated ion pair in solution; Scheme 1). 45 While the low-temperature 1 H NMR spectra for both compounds are very similar, the extent of line-broadening for the diastereotopic benzyl-CH 2 group at a given temperature is quite different between the two, which indicates that these compounds have distinct exchange rates.…”
Section: Resultsmentioning
confidence: 99%
“…41 Previously, we described that main group (B and Al) complexes with these ligands can accept up to two electrons, and that these reduction products subsequently react with electrophiles (e.g., Bn + or H + ) to form new N-C and N-H bonds at the formazanate ligand (Scheme 1). [42][43][44][45] Furthermore, we have demonstrated that the [2e − /E + ]-equivalent 'stored' at the ligand could be converted to E • radicals via homolytic cleavage of the N-C (Bn) and N-H bonds, respectively. 43 In a recent paper, the structural features and homolytic bond dissociation energies of ligand-benzylated B and Al complexes were reported.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Comparison of structure, bonding, and reactivity of AlPh 2 complex 84 2À with its BPh 2 analogue 76 2À , both possessing formazanate ligands in their trianionic form, led to several important conclusions. 98 (i) The Al-N bonds have primarily ionic character and B-N bonds have primarily covalent character. (ii) The introduction of an Al ion resulted in N-C aryl bonds with significant p character; a structural feature that appears to have been recently exploited to induce near-IR absorption and emission in similar compounds.…”
Section: Group 12 (Zn)mentioning
confidence: 99%